Analysis of Needs Training Design Assistance in Developing Teaching Modules in the Freedom of Learning Curriculum for Primary Schools Teachers at the Kuningan Regency Education Office, West Java - Budi Setiawan; Laksmi Dewi; Asep Herry Hernawan; Dadang Sukirman; Nurul Laily Al Arsuadhi; Rizal Kailani; Maurra Syifah Wijaya; Chevy Kusumah Wardhana; Gupi Rohman Nurmansyah; Azizah Nurul Khairunnisa; Juwintar Febriani Arwan (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
This study aims to provide a basis need analysis for the curriculum module provision, training form and training time of elementary school teachers in Kuningan regency, West Java and understand the needs of the their' participation in new curriculum training. Sixty teachers in Kuningan regency were selected for a group interview. Based on the interview results, the researchers designed a questionnaire. They were from the same school levels in Kuningan regency that applied freedom of learning curriculum. It made us decided to use or adopt cluster random sampling method. They were surveyed through a web questionnaire. In total, 80% of the respondents believe that the self-opening aspect of the module needs to be carried out in four items. Secondly, for the explorative concept within the module, it was found that 70% respondents showing their believe that it was crucial to include further explanation and discussion. Next, on the collaborative space, it showed that 85% respondents found to be agree on the items of grouping and discussion and presentation within the module. Fourthly, it was found that 85% respondents shared their agreement on the guided reflection aspect in the module. In the new freedom of learning curriculum, it is found that the elementary school teachers in Kuningan regency have proper understanding within the module. It shows that they have identified the components within the module should cover those six crucial aspects.